Landasan dan Fondasi Dasar Tatakelola Pendidikan Islam Dalam Analisis Aspek-Aspek Filosofis - Razali, Ruslan; Asrul, Asrul (Al-Ikhtibar: Jurnal Ilmu Pendidikan, 2024)
This study examines the main aspects of philosophy studies that are directly the basis for the implementation and development of governance in the field of education. The substance, approach and ontological, epistemological and axiological viewpoints in the development of Islamic education governance are critically analyzed and offered to be the foundation and basic for institutional revitalization and education policy reform in the current era of openness. This study is a conceptual study in which the data sources and references are formulated through library review and studied in depth with patterns and methods of content analysis. The formulation of this study illustrates that; 1). The essence of Islamic educational governance emphasizes the importance of balancing rational thinking with spiritual values, mastery of reason in the tradition of science with the firmness of spirituality. 2). The foundation must adopt a comprehensive approach to cognitive development, prioritizing affective growth especially values and attitudes and actions in real application. Educational governance must support the independence of the students, provide space to develop into progressive, creative, and innovative individuals, adapting to the changing times and environment. 3). The urgency of integrating leadership and managerial principles into a strong, dynamic, independent, and innovative personal character. And actions based on Islamic principles that are reflected in the value of worship, the value of ikhsan, the value of ukhrawi orientation, the value of rahmatan lil'alamin, positivity, long-term thinking, tawakkal.